2020
DOI: 10.3390/d12060254
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities in the Fynbos Region of South Africa: What Happens during Woody Alien Plant Invasions

Abstract: The Cape Floristic Region (CFR) is globally known for its plant biodiversity, and its flora is commonly referred to as fynbos. At the same time, this area is under severe pressure from urbanization, agricultural expansion and the threat of invasive alien plants. Acacia, Eucalyptus and Pinus are the common invasive alien plants found across the biome and considerable time, effort and resources are put into the removal of invasive alien plants and the rehabilitation of native vegetation. Several studies have sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 129 publications
(210 reference statements)
0
5
0
Order By: Relevance
“…It is well known that alien plants may become a potential threat and cause damage to ecosystems [58,59], while in the present study, we found that nonnative plant populations may impact the microbial community and function of water bodies. Invasive plants have previously been found in terrestrial ecosystems to affect soil chemistry and microbial communities [60], but they have rarely been reported before in aquatic ecosystems. Alien organisms may change local microbial communities by affecting the properties of local conditions [61,62] and altering the phyllospheric and rhizosphere microbial characteristics [63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that alien plants may become a potential threat and cause damage to ecosystems [58,59], while in the present study, we found that nonnative plant populations may impact the microbial community and function of water bodies. Invasive plants have previously been found in terrestrial ecosystems to affect soil chemistry and microbial communities [60], but they have rarely been reported before in aquatic ecosystems. Alien organisms may change local microbial communities by affecting the properties of local conditions [61,62] and altering the phyllospheric and rhizosphere microbial characteristics [63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…The microbial community structure in the fynbos is rather complex and includes bacteria, fungi and archaea. These microbes play a vital role in supporting plant growth in the acidic, nutrient-poor soils of the fynbos [ 28 , 31 ]. This study was conducted to ascertain any changes in microbial community structure during wet and dry seasons, and the results showed that the phylum Actinobacteria was very dominant (≥30%) in the rhizosphere of Polhillia , Wiborgia and Wiborgiella species during both wet and dry seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of microbial community structure associated with endemic plant species in the Cape fynbos [ 6 , 25 , 26 , 27 , 28 ] have revealed high microbial diversity belowground, similar to aboveground plant species diversity. Microbial diversity can however be altered by many factors, including soil pH, plant species/type, plant age, cultivation history, as well as growth season [ 6 , 25 , 26 , 27 , 28 ]. The rhizosphere of legumes in the fynbos can therefore differ from plant to plant and species to species during different seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the species can establish a symbiotic partnership with many soil arbuscular mycorrhizal fungi (AMF). These fungal symbionts are the most widespread on the surface of the globe and adapted to many environments and different host plants (Vaishnav et al, 2017;Jacobs et al, 2020); they can form mutualistic associations with the roots of about 80% of terrestrial plants (Smith and read 2008). Golden wreath wattle (A. cyanophylla Lindl or A. saligna Labill) is a species native to the temperate region of southwestern Australia, where it has a naturally widespread distribution (Millar and Byrne, 2012) in various habitats, especially on soils with a high proportion of sand, such as dunes, sandy plains, or rocky ridges where it forms open forests (Griffin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%